The Urgency of Guaranteeing the Protection of Women’s Rights in Afghanistan Post-Taliban Leadership Based on International Human Rights Principles - Ikhsana, Lisa; Khasanah, Eka Imroatun (Jurnal Scientia Indonesia, 2020)
Human rights are rights that humans have solely because they are human. After the leadership of the Taliban in Afghanistan, the world community is worried about the protection of human rights for the female population in Afghanistan. The reason is that many human rights violations were committed against the female population in Afghanistan that were carried out during the current leadership of the Taliban, such as restrictions on access to education and prohibitions from working. Of course, this problem is enough to get the world's attention because it is considered to violate international human rights principles, which include the principle of equality, the principle of non-discrimination, and the principle of state obligations. Based on this, there is a sense of concern from countries in the world to voice this conflict in various world forums and organizations, one example is The United Nations Entity for Gender Equality and the Empowerment of Women for gender equality or commonly known as UN Women, namely the United Nations agency defending gender equality and empowering women in the world.